THE EFFECT OF GINKGO BILOBA AGAINST OTOTOXIC HEARING LOSS ON ADVANCED STAGE UNDIFFERENTIATED NASOPHARYNGEAL CARCINOMA RECEIVING CISPLATIN CHEMOTHERAPY - Hendriyanto, Donny; Setiamika, Made; Primadewi, Novi (TALENTA PUBLISHER, 2020)
Abstract Introduction: Undifferentiated nasopharyngeal carcinoma is the most common malignant tumor in nasopharynx, in which most patients come to a hospital in advanced stage. Cisplatin is one of the most effective widely used chemotherapy drugs for advanced stage undifferentiated nasopharyngeal carcinoma. Although it provides a successful outcome against cancer, there is serious side effect namely ototoxic hearing loss. Ginkgo biloba is a powerful antioxidant which may prevent ototoxic hearing loss. Objective: The study aims to determine the effect of ginkgo biloba against ototoxic hearing loss on advanced stage undifferentiated nasopharyngeal carcinoma receiving cisplatin chemotherapy. Methods: This study was double blind Randomized Control Trial with pre-post test design, was conducted in 22 patients with advanced stage undifferentiated nasopharyngeal carcinoma receiving cisplatin chemotherapy at the Department of Otorhinolaryngology Head and Neck Surgery dr. Moewardi Hospital Surakarta between June 1st and October 1st 2019. The subjects were allocated into control (plasebo) and treatment (80 mg Ginkgo biloba extract) groups. Hearing function was examined with pure tone audiometry, tympanometry and Distortion Product Otoacoustic Emission before and after the first, the second and the third cisplatin chemotherapy. The results of the examination of the two groups were tested using Friedman and Chi Square test. P value of <0.05 was considered significant. Results: The study subjects were mostly male (63.6%), with the age range of 40-59 years (90.9%). The baseline characteristics of the study subjects were homogeneous (p>0.05). There was a significant difference in the incidence of ototoxic hearing loss between control and treatment group after getting the second and the third chemotherapy (p=0.043 and p=0.033, respectively). Conclusion: There is a significant effect of ginkgo biloba in term of preventing ototoxic hearing loss on advanced stage undifferentiated nasopharyngeal carcinoma patients receiving cisplatin chemotherapy.